Development of Learning Media Based on Smart Apps Creator - Khasanah Khasanah; Rusman Rusman (AL-ISHLAH: Jurnal Pendidikan, 2021)
The presence of technology should be able to penetrate the limitations of space and time in improving the quality of learning. This study aims to develop learning media for Smart Apps Creator (SAC), determine the level of Validity and Reliability of Smart Apps Creator (SAC) media products, and determine the efficiency of Smart Apps Creator (SAC) media products. This research was conducted at SMK Sandikta Bekasi City. This research method uses the ADDIE model approach which has five steps, namely Analyze, Design, Develop, Implement, and Evaluate. The development of media based on Android Smart Apps Creator (SAC) uses Al-Quran material as a way of life. The validation of this development product was carried out by three media experts and three material experts and continued with a one-on-one trial of three students and a small group trial of three people. The results of the research and development that have been carried out have produced a physical model of learning media products based on Android SAC (Smart Apps Creator). The results of the validation of the validators stated that the media was suitable for use in class XI SMK students. With the respective eligibility rates of 85% and 83%. SAC product efficiency The development of SAC media has been effective but not yet maximized. This is due to the limited hosting capacity to accommodate all materials and materials that are more complex. This can be seen from the effectiveness test of 58% pre-test and 86% post-test, so there is an average difference of 28%.